The dual influence of whole-body vibration on the total peripheral resistance - Yue, Z.; Kleinöder, H.; de Marees, M.; Mester, J. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Whole-body vibration, as a special training approach, has attracted attention for decades. Various potential benefits and risks have been claimed in the literature. How ever, the mechanisms for the potential benefits and risks are still poorly understood. The influence of whole-body vibration on blood circulation is an important aspect of the matter. Although some experimental and theoretical studies on this topic have been published (cf. the references below), the detailed time curves of various cardiovascular parameters, particularly of the total peripheral resistance (TPR), during whole-body vibrations under different conditions have never been published before. Superficially, some results may look contradictory to each other. However, if we put all the results together and take the different conditions in different measurements into account, we will get a clear and unified picture as follows. The influence of whole-body vibration on TPR is not a simple matter. Instead, it has a dual property: on the one hand, the whole-body vibration tends to increase TPR through the increase of viscosity, while on the other hand, the body may react to the whole-body vibration by the dilation of small vessels, particularly the dilation of arterioles, under certain conditions. This would greatly reduce TPR. Even if the body posture is fixed during the whole-body vibration, the TPR vs. time curves for different subjects may behave very differently. This means that different individuals may react to the two sides of the dual influence differently. Whether TPR increases or decreases at a certain period for a given subject depends on which side of the dual influence dominates over the other side. If the body posture is not fixed, but changes suddenly during the whole-body vibration, so that the transmissibility of vibration would increase considerably during the change of the body posture, we always find considerable decrease of TPR caused by such sudden changes of body posture. Statistical analysis confirms the significance of this finding. In summary, all the experimental and theoretical results support the conclusion of the dual influence of whole-body vibration on TPR as above-stated.